Pola Saluran Pemasaran Ayam Kampung Konsumsi di Kecamatan Kalirejo Kabupaten Lampung Tengah - Wahyu Setiawan; Herawati M; Abdurrahman US (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2019)
The purpose of this study was to determine the channel patterns and marketing margins of native chickens in Kalirejo Sub Regency, Central Lampung Regency. The location of the study was conducted in 5 villages (Kalirejo, Poncowarno, Sribasuki, Kaliwungu, Sridadi). The method used in this research is descriptive analytic method, which is a method that aims to solve problems that exist at the present time by collecting data, compiling, managing, analyzing, describing and drawing conclusions. The population and sample are farmers and traders in the Kalirejo area with sampling techniques using snowball sampling techniques. Analysis of the data in the study using descriptive method while quantitative data was conducted to determine the amount of marketing margins and the farmer's share received by farmers. The research results revealed that there were 3 patterns of marketing channels in Kalirejo Sub Regency namely pattern 1) farmers-wholesalers-wholesalers-retailers-consumers; pattern 2) breeders-wholesalers-retailers-consumers; and pattern 3) breeders-retailers-consumers. The most profitable marketing margin for consumption chicken breeders is the one with the lowest margin percentage value of 16.67% in marketing channel III. The most efficient marketing channel is marketing channel III because it has the lowest total marketing margin (Rp.5,000 per head) with the highest Farmer’s share (91.30%). Keywords: Native Chicken, Marketing Pattern